Remission of alcohol use disorder following traumatic brain injury with focal orbitofrontal cortex hemorrhage: case report and network mapping - Haque, Saarah; Bellmunt-Gil, Albert; Davidson, Benjamin; Luscher, Christian; Fox, Michael D.; Joutsa, Juho; Burke, Matthew J. (Nature Portfolio, 2025)
Background: The orbitofrontal cortex (OFC) and its role in the regulation of urges/compulsion has been identified as a critical component of circuit-based addiction models. Building on such models, it was recently shown that brain lesions disrupting addictive behavior can be mapped to a common brain circuit.
Methods: We present a case of a 42-year-old woman with chronic treatment-refractory alcohol use disorder who experienced early remission following a traumatic brain injury (TBI) with focal left OFC intracerebral hemorrhage. Using a network mapping approach (normative connectome, n = 1000), functional connectivity was computed from the traced OFC lesion across all brain voxels.
Results: The case lesion map topography converges on a brain lesion map previously described as disrupting addictive behavior, but with an inverse connectivity profile (spatial correlation r = -0.59). This spatial correlation is more negative than what would be expected by chance (permutation test 1-sided, p = 0.04) or by random lesion cases (1-sided, p < 0.001).
Conclusions: Based on these results, we suggest that potentially just disrupting this brain network, regardless of the directionality, could facilitate remission. However, this case report cannot control for multiple psychosocial factors potentially impacting alcohol remission and caution is also needed for considering TBI as a mechanism for generating an isolated focal lesion. Overall, this case contributes to our understanding of circuit-based models of addictive behavior and could be useful in generating hypotheses for neuromodulatory treatment strategies.